2019
DOI: 10.1042/bcj20180545
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-dependent calmodulin binding to cardiac ryanodine receptor (RyR2) calmodulin-binding domains

Abstract: The Ca2+ sensor calmodulin (CaM) regulates cardiac ryanodine receptor (RyR2)-mediated Ca2+ release from the sarcoplasmic reticulum. CaM inhibits RyR2 in a Ca2+-dependent manner and aberrant CaM-dependent inhibition results in life-threatening cardiac arrhythmias. However, the molecular details of the CaM–RyR2 interaction remain unclear. Four CaM-binding domains (CaMBD1a, -1b, -2, and -3) in RyR2 have been proposed. Here, we investigated the Ca2+-dependent interactions between CaM and these CaMBDs by monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 52 publications
3
49
0
Order By: Relevance
“…This is consistent with CaM binding to CaMBD and Ca 2+ binding to CaM being thermodynamically coupled [5,32,[35][36][37], and this enabled an estimation of CaM's affinity for binding to Ca 2+ when complexed with RyR2(R3581-L3611), i.e. estimating CaM's sensitivity to Ca 2+ when already bound to RyR2 CaMBD [5,6,31]. To this end, the FA measurements for the titration of CaM and peptide at constant concentrations (fixed ratio) with Ca 2+ were extracted from the larger titration data sets (Fig.…”
Section: Arrhythmogenic Cam Mutations Alter the Ca 2+dependency Of Thsupporting
confidence: 70%
See 1 more Smart Citation
“…This is consistent with CaM binding to CaMBD and Ca 2+ binding to CaM being thermodynamically coupled [5,32,[35][36][37], and this enabled an estimation of CaM's affinity for binding to Ca 2+ when complexed with RyR2(R3581-L3611), i.e. estimating CaM's sensitivity to Ca 2+ when already bound to RyR2 CaMBD [5,6,31]. To this end, the FA measurements for the titration of CaM and peptide at constant concentrations (fixed ratio) with Ca 2+ were extracted from the larger titration data sets (Fig.…”
Section: Arrhythmogenic Cam Mutations Alter the Ca 2+dependency Of Thsupporting
confidence: 70%
“…These serial titration curve analyses showed that CaM‐WT even without Ca 2+ (< 0.3 n m [Ca 2+ ] free ), bound to RyR2(R3581–L3611) with moderate affinity ( K D 1.4 μ m ) and that the CaM‐RyR2(R3581–L3611) interaction was extremely [Ca 2+ ] free ‐dependent (very steep decline in K D as a function of [Ca 2+ ] free ) with the K D decreasing approximately 1200‐fold to 1.1 n m over the [Ca 2+ ] free range 0.01–10 μ m . In the presence of RyR2(R3581–L3611) both the N‐ and C‐domain of CaM‐WT are fully Ca 2+ ‐bound at 10 μ m [Ca 2+ ] free and above, and no further increase in affinity with increasing [Ca 2+ ] free was observed above 10 μ m [Ca 2+ ] free . All arrhythmogenic CaM mutants retained a moderate affinity for binding to the RyR2 CaMBD both without Ca 2+ ( K D 1–2 μ m ), and also showed high affinity binding with 10 μ m [Ca 2+ ] free ( K D 1–8 n m ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether CaM‐N54I binding to RyR2 CaMBDs differs from that of the CaM‐WT, we measured the affinity of CaM‐WT and ‐N54I for binding to peptides representing each of the RyR2 CaMBDs (Table ). Because these interactions are strongly dependent on the [Ca 2+ ] free , we measured CaM’s affinity for binding to each peptide in a physiologically relevant [Ca 2+ ] free range (~ 0.05–400 µ m ) . This was done by titrating fluorescently labeled peptides with CaM in [Ca 2+ ] free ‐buffered solutions and monitoring the extent of CaM binding to the peptides using the change in peptide fluorescence anisotropy (FA).…”
Section: Resultsmentioning
confidence: 99%
“…By fitting these FA titration curves to a stoichiometric binding model, we obtained the affinity of CaM for binding to each peptide expressed as that interaction’s dissociation constant ( K D ) at each [Ca 2+ ] free (Fig. ) . A low K D equates to extensive protein–peptide complex formation and thus a high‐affinity interaction (see ‘Materials and methods’).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation